A Novel Echocardiographic Method for the Detection of Subclinical Atherosclerosis in Newly Diagnosed, Untreated Type 2 Diabetes. Issue 6 (24th January 2013) - Simsek, Hakki; Sahin, Musa; Gunes, Yilmaz; Dogan, Adnan; Gumrukcuoglu, Hasan Ali; Tuncer, Mustafa
Abstract : Background: Diabetes accelerates the natural process of atherosclerosis and is a predictor for progression of atherosclerotic lesions. To improve clinical outcomes, noninvasive imaging modalities have been proposed to measure and monitor atherosclerosis. Recently, it has been shown that the color M‐mode–derived propagation velocity of the descending thoracic aorta (aortic velocity propagation [AVP]) was associated with coronary and carotid atherosclerosis. Methods: Carotid intima‐media thickness (CIMT) and AVP were measured in 72 patients with newly diagnosed type 2 diabetes and 44 healthy people. Individuals who had previously used oral hypoglycemic agents or insulin treatment or had a history of hyperlipidemia, cigarette smoking, hypertension, and cardiovascular disease were excluded from this study. Results: Compared with control group, patients with type 2 diabetes had significantly lower AVP (39.9 ± 6.5 vs. 58.4 ± 6.7 cm/sec, P < 0.001) and higher CIMT (1.1 ± 0.1 vs. 0.95 ± 0.12 mm, P < 0.001) measurements. There were significant correlations between AVP and CIMT (r = −0.835, P < 0.001), AVP and fasting plasma glucose (r = −0.796, P < 0.001)), AVP and HbA1 c (r = −0918 P < 0.001). Conclusions: Diabetes mellitus may be associated with subclinical atherosclerosis assessed by measurement of AVP and CIMT. These simple methods might improve patient selection for primary prevention atherosclerotic progression.